Improving Students’ Higher Order Thinking Skill with STEM-Oriented E-Module - Chidayati, Nurul; Distrik, I Wayan; Abdurrahman, Abdurrahman (Indonesian Journal of Science and Mathematics Education, 2021)
The aim of this research is to develop a practical and effective STEM-oriented e-module to improve students' higher order thinking skills. This research uses research and development method with ADDIE model. Data collection techniques used test and non-test instruments by analyzing the feasibility, practicality, and effectiveness of the product. The results showed that the average value of content validity was 82.2% and the average value of construct validity was 83.9%, thus indicating that this product is suitable for use as teaching materials. Based on the results of the practicality test, the average value of the practicality of this product is 76.3%. Meanwhile, based on the results of the product effectiveness test, 27 students gave a score of 77.8%, which means this product is effective for use as teaching materials. The N-Gain score from the application of this product is 0.45 which means there is an increase in the moderate category. Based on the results of the study, it was concluded that this STEM-oriented e-module is feasible, practical, and effective to be used as a stimulus to train students' higher-order thinking skills during the covid-19 pandemic.